La duración como dimensión temporal en los reportajes radiofónicos - Pérez Esain, Crisanto; Herrera Damas, Susana (Área Abierta. Revista de comunicación audiovisual y publicitaria, 2007)
Although for time and economic reasons, the radio news feature is not as extended as other radio genres, it is a very necessary and useful text in the present time. Thanks to it we can know the facts with greater depth, offer a greater perspective and locate the information in an ampler context. In its elaboration, one of the main elements is the style and within this one the treatment of the time. This last aspect, can be studied through three dimensions: the order, the duration and the frequency. The aim of this article is to analyze the duration like one of the temporary dimensions when elaborating news features in radio. As we will see, when necessary, the reporter may use different sorts of resources, such as elipsis, summaries, scenes, pauses or digresions, with all the expressive variants that these modalities offer. In all the cases we will be illustrating with real examples the diverse modalities so that they can be better understood